Age differences in physical activity intentions and implementation intention preferences - Alley, S.; Schoeppe, S.; Rebar, Amanda; Hayman, M.; Vandelanotte, C. (Springer New York LLC, 2018)
© 2017, Springer Science+Business Media, LLC. This study aimed to examine older adults’ physical activity intentions and preferred implementation intentions, and how intentions and preferred implementation intentions differ between older, middle aged and younger adults. A cross-sectional Australian wide telephone survey of 1217 respondents was conducted in 2016. Multiple and ordinal regression analyses were conducted to compare intentions and preferred implementation intentions between older (65 +), middle aged (45–64) and younger adults (< 45). A higher percentage of older adults had no intentions to engage in regular physical activity within the next 6 months (60%) compared to younger adults (25%). Older adults’ most popular preferences included being active at least once a day and for 30 min or less and were more likely to prefer more frequent and shorter sessions compared to younger adults. Both older and middle aged adults were more likely to prefer slower paced physical activity compared to younger adults who preferred fast paced physical activity. Physical activity interventions for older adults should address the high percentage of older adults with no intentions and public health campaigns for older adults should promote 30 min daily sessions of slow paced activity.